Предмет: Алгебра,
автор: muslimat007
Сделайте побыстрее по. ??????
Приложения:
Ответы
Автор ответа:
0
=(cos² a -sin² a +cos²a +sin² a)*(sin²a/cos²a) -1 = 2cos²a * (sin² a/cos²a) -1 = 2sin² a - sin²a - cos²a = -(cos²a - sin²a) = -cos2a
Ответ: 4)
Ответ: 4)
Автор ответа:
0
Спс
Похожие вопросы
Предмет: Математика,
автор: lamiyemrahova2007
Предмет: Русский язык,
автор: vika68033
Предмет: Математика,
автор: vajlettkorcagina
Предмет: Информатика,
автор: tttuffdjfthrf
Предмет: Математика,
автор: popovayi1168